2019
DOI: 10.1074/jbc.ra118.004538
|View full text |Cite
|
Sign up to set email alerts
|

Blood–brain and blood–cerebrospinal fluid passage of BRICHOS domains from two molecular chaperones in mice

Abstract: Edited by Ursula JakobTargeting toxicity associated with ␤-amyloid (A␤) misfolding and aggregation is a promising therapeutic strategy for preventing or managing Alzheimer's disease. The BRICHOS domains from human prosurfactant protein C (proSP-C) and integral membrane protein 2B (Bri2) efficiently reduce neurotoxicity associated with A␤42 fibril formation both in vitro and in vivo. In this study, we evaluated the serum half-lives and permeability into the brain and cerebrospinal fluid (CSF) of recombinant hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…BRICHOS is a recently established molecular chaperone domain, which efficiently prevents fibrillar amyloid aggregation as well as its associated toxicity, as shown in vitro, in mouse hippocampal slice preparations, and in Drosophila models 19,23,26,27,32,34,35 . The dementia relevant Bri2 and its BBB permeable BRICHOS domain are associated with AD: Bri2 is produced in the CNS in the same cells as the Aβ precursor protein AβPP, colocalizes with senile plaques, interacts with Aβ in neurons, and increased amounts of different Bri2 forms have been found in human AD brains 38,39,48 . Further preclinical work that focus on the potential usefulness of Bri2 BRICHOS delivery and/or activation for prevention and treatment of AD should be pursued in relevant animal models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BRICHOS is a recently established molecular chaperone domain, which efficiently prevents fibrillar amyloid aggregation as well as its associated toxicity, as shown in vitro, in mouse hippocampal slice preparations, and in Drosophila models 19,23,26,27,32,34,35 . The dementia relevant Bri2 and its BBB permeable BRICHOS domain are associated with AD: Bri2 is produced in the CNS in the same cells as the Aβ precursor protein AβPP, colocalizes with senile plaques, interacts with Aβ in neurons, and increased amounts of different Bri2 forms have been found in human AD brains 38,39,48 . Further preclinical work that focus on the potential usefulness of Bri2 BRICHOS delivery and/or activation for prevention and treatment of AD should be pursued in relevant animal models.…”
Section: Discussionmentioning
confidence: 99%
“…To test this hypothesis, we coincubated rh Bri2 BRICHOS R221E monomers and rh wild-type Bri2 BRICHOS oligomers, after which the distribution of Bri2 BRICHOS assembly states, and effects on Aβ42 fibril formation and neurotoxicity were evaluated. To enable differentiation between wild-type and R221E rh Bri2 BRICHOS monomers, we used a rh wild-type Bri2 BRICHOS construct containing an AU1 tag, which behaves like the non-tagged wild-type protein and can be selectively immunodetected using an anti-AU1 antibody 48 . Native PAGE and western blot analysis showed that coincubation of rh wildtype Bri2 BRICHOS oligomers with rh Bri2 BRICHOS R221E monomer lead to the release of smaller species, especially monomers ( Fig.…”
Section: R221e Mutant Forms Stable Monomers and Unstable Oligomersmentioning
confidence: 99%
“…Rh Bri2 BRICHOS has emerged as an interesting biopharmaceutical candidate for treating AD, as the domain is a potent inhibitor of Aβ42 amyloid fibril formation and in particular its associated neurotoxicity in vitro, in hippocampal slice preparations ex vivo , and in Drosophila models in vivo [ 15 ] . In addition, rh Bri2 BRICHOS passes the blood-brain barrier [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Bri2 BRICHOS prevents amyloid formation and neurotoxicity of the 42-residue Aβ42, the main amyloidogenic species in AD, in transgenic fruit flies and mice and prevents Aβ42 neurotoxicity in mouse hippocampal slices in vitro [ 12 15 ]. Moreover, recombinant human (rh) Bri2 BRICHOS passes the blood-brain barrier in wild-type mice, making parenteral administration of rh Bri2 BRICHOS an interesting new potential treatment against AD [ 16 , 17 ]. Such application of rh Bri2 BRICHOS would require industrial protein production and purification protocols that result in a homogenous product at a reasonable cost.…”
Section: Introductionmentioning
confidence: 99%
“…The Bri2 protein is produced in the central nervous system, in the same cells as the Aβ precursor protein, APP, and colocalizes with senile plaques, interacts with Aβ in neurons, and increased amounts of different Bri2 forms have been found in human AD brains [81,82]. Interestingly, other researchers have found that the BRICHOS domain from the Bri2 chaperone is BBB permeable, reaching the brain parenchyma after peripheral administration [83]. A single point mutation of Bri2 BRICHOS, the mutant R221E, forms stable monomers and selectively blocks a main source of toxic species during Aβ42 aggregation.…”
Section: Mechanisms Involved In Transthyretin Neuroprotection In Alzhmentioning
confidence: 99%